Advancing equity via research-practice partnerships: a theory of action for equity-centered RPPs - Welsh, Richard O.; James McGraw, Kathryn (Frontiers in Education, 2025)
IntroductionResearch-practice partnerships (RPPs) are posited as a vehicle to improve the use of research evidence. Equity-centered RPPs are an evolving subset of RPPs loosely bound by equity principles and varying in partnership design and approaches. There is a need for a better understanding of the partnership dynamics and activities of equity-centered RPPs, as well as whether and how equity-centered RPPs improve youth outcomes.MethodsWe leverage the growing literature on the use of research evidence, RPPs, and improvement research to provide an interdisciplinary framework that connects the dynamics and activities of equity-centered RPPs to proximal and distal outcomes.ResultsWe argue that equity-centered RPPs are RPPs that center race and racism in their composition, goals and approaches to research. Explicitly attending to race and power in partnership dynamics and activities, centering children marginalized by oppression, and embracing historical perspectives are hallmarks of equity-centered RPPs. By first attending to equitable processes (i.e., dynamics and activities), equity-centered RPPs create the conditions for equitable outcomes – for RPP participants and the students and schools they serve. We posit that the theory of racialized organizations centers the role of race in partnership dynamics, activities and outcomes of equity-centered RPPs and social design experiments capture the disposition of equity-centered RPPs of advancing equity through learning via the production and use of research evidence.DiscussionWe conclude with a discussion of how this theory of action can be useful for those participating in and studying equity-centered RPPs.